The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1590/s1519-38292002000100005
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo das indicações de cesariana entre um hospital público-universitário e um hospital privado

Abstract: OBJETIVOS: analisar a incidência e as indicações de cesariana realizadas no Hospital Escola da Falculdade de Medicina do Triângulo Mineiro e um hospital privado, ambos localizados em Uberaba, Minas Gerais, Brasil. MÉTODOS: trata-se de estudo transversal desenvolvido a partir da coleta nos prontuários dos hospitais, consistindo da idade, procedência, situação conjugal, escolaridade, paridade e indicações de cesariana. RESULTADOS: a incidência de cesariana foi de 24,3% no Hospital Escola contra 89,2% no hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
9

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 3 publications
(2 reference statements)
0
6
0
9
Order By: Relevance
“…The type of birth to which the adolescents were submitted clearly shows this dichotomy. Studies (14)(15) show a high rate of c-sections in Brazil, mainly due to inadequate medical care, pregnant women's precarious education, causes of economic nature, among others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The type of birth to which the adolescents were submitted clearly shows this dichotomy. Studies (14)(15) show a high rate of c-sections in Brazil, mainly due to inadequate medical care, pregnant women's precarious education, causes of economic nature, among others.…”
Section: Discussionmentioning
confidence: 99%
“…This increase is progressive and exaggerated, and occurs especially among the socioeconomic favored classes, who attend private clinics and/or have health plans, while these indexes are lower among the economically less favored classes, whose deliveries mainly occur in public hospitals or teaching hospitals (14) . Table 3 It is important to appoint that the index of csections tolerated by the Ministry of Health is 15 to 20%, and that the current high rate of c-sections constitutes a public health problem, since it has led to higher rates of maternal and perinatal morbidity and mortality (16) .…”
Section: Discussionmentioning
confidence: 99%
“…No Brasil, no entanto, o número de cesáreas cresce de modo desproporcional às referidas indicações, e se observa que há maior indicação de cesárea associada à categoria de internação hospitalar privada e pré-paga e ao aumento do padrão social das gestantes do que ao risco obstétrico propriamente dito (FABRI et al, 2002;FAÚNDES;CECATTI, 1993;HOPKINS, 2000;HOPKINS et al, 2005;MORAIS;GOLDENBERG, 2001;VILLAR et al, 2006;YAZLLE et al, 2001).…”
Section: Saúde Reprodutiva Da Mulher No Brasilunclassified
“…Brazil has one of the world's highest rates of C-section births (WHO 1985, Víctora et al 2011 and prevalence is higher among private hospitals than the public health system (Faúndes & Cecatti 1991, Yazlle et al 2001Fabri et al 2002, Faúndes et al 2004, Haddad & Cecatti 2011 This suggests that the higher on the economic scale, the more autonomy the woman has for choosing this kind of procedure, even if it is more risky. C-sections are considered to involve risk, but risk is inherent to any pregnancy.…”
Section: Risk: a Polyvalent Categorymentioning
confidence: 99%
“…Women are not at risk of death and may take pregnancy to full term without harm to their 6 In their study of 86,120 births in the city of Ribeirão Preto (São Paulo State) between 1986 and 1995, Yazlle et al (2001) found the C-section rate to be 32.1% in public hospitals, and 81.8% in private hospitals. Fabri et al (2002) compared the rate of C-sections between one public and one private hospital located in the state of Minas Gerais in 1996, and found that C-sections accounted for 24.3% of births in the public hospital against 89.2% in the private hospital. Haddad and Cecatti (2011) found that the rate of C-sections in Brazil in 2006 was 30.1% in the public system versus 80.7% in private hospitals.…”
Section: Risk: a Polyvalent Categorymentioning
confidence: 99%